2016
DOI: 10.1007/s00256-016-2533-1
|View full text |Cite|
|
Sign up to set email alerts
|

Osteitis: a retrospective feasibility study comparing single-source dual-energy CT to MRI in selected patients with suspected acute gout

Abstract: ObjectiveDual-energy computed tomography detects tophi in patients with chronic gout. However, other information that can be obtained from the same scan is not the focus of the current research, e.g., the detection of bone marrow edema (BME) using virtual bone marrow imaging (VBMI). The aim of this study was to evaluate if BME in patients with acute arthritis can be detected with VBMI using magnetic resonance imaging (MRI) as the standard of reference.Materials and methodsThis retrospective study included 11 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…To our knowledge, this is the first prospective study applying DECT as a novel imaging technique for detection of BMEL in RA 8. We found that the colour-coded DECT maps differentiate normal bone marrow from BMEL and corresponded well to BME on MRI.…”
mentioning
confidence: 59%
“…To our knowledge, this is the first prospective study applying DECT as a novel imaging technique for detection of BMEL in RA 8. We found that the colour-coded DECT maps differentiate normal bone marrow from BMEL and corresponded well to BME on MRI.…”
mentioning
confidence: 59%
“…Likewise, standard CT is insensitive to marrow edema or inflammation, although in the future, dual-energy CT may be able to detect and potentially quantify osteitis. Preliminary pilot studies have investigated this application in patients with gout [96] and RA [97].…”
Section: Bone Inflammationmentioning
confidence: 99%
“…89%) for visual inspection and quantification, respectively, of bone marrow edema affecting the sacroiliac joints in patients with spondyloarthritis. 45 The detection of virtual bone marrow edema by DECT led to the diagnosis of acute arthritis 54 and active RA in the hand and wrist. 55 Finally, Fukuda et al, using iodine overlay images, demonstrated that DECT can be applied successfully for the investigation of small joints in patients with RA and PSA.…”
Section: Dual-energy Computed Tomographymentioning
confidence: 99%